Theoretical Investigation of Friction at Die/Billet Interface in Hydrostatic Extrusion of Commercially Pure Aluminum. (2016) - Tomar, Pankaj
Abstract: The investigation of friction at the die billet interface in hydrostatic extrusion process is vital issue as it is affected by various operating conditions. In presence of pressurized lubricant chamber or hydrostatic extrusion pressure a lubricant film is formed at the interfacial contact in hydrostatic extrusion process. Existence of lubricating film at the interfacial contact drastically reduces friction and its optimization is needful as thick lubricating film produces unconstrained deformation on the billet surface and thin lubricating film enhances friction on the interfacial contact. Therefore, the purpose of this paper is to carry out theoretical investigation of friction at die/billet interface in hydrostatic extrusion process of commercially pure aluminum under various operating parameters using a Roelands' viscosity model. The Tresca's friction factors at the interfacial contact of die/billet increases on increase of semi-die angle of die and decreases on increase of extrusion pressure due to more favourable lubrication conditions.